YME1L degradation reduces mitochondrial proteolytic capacity during oxidative stress - Rainbolt, T Kelly (EMBO Rep, 2015)
Mitochondrial proteostasis is maintained by a network of ATP-dependent quality control proteases including the inner membrane protease YME1L. Here, we show that YME1L is a stress-sensitive mitochondrial protease that is rapidly degraded in response to acute oxidative stress. This degradation requires reductions in cellular ATP and involves the activity of the ATP-independent protease OMA1. Oxidative stress-dependent reductions in YME1L inhibit protective YME1L-dependent functions and increase cellular sensitivity to oxidative insult. Collectively, our results identify stress-induced YME1L degradation as a biologic process that attenuates protective regulation of mitochondrial proteostasis and promotes cellular death in response to oxidative stress.